Learning Management based on Gender Responsive Segregation at MA Raudlatul Ulum - Majda, Nadia Ela; Utaminingsih, Sri; Ismaya, Erik Aditia (jfpublisher, 2022)
The researh entitled Learning Management based on Gender Responsive Segregation is considered important study in education since many people clash with religious dogma with segregation in education, it is necessary to review how the implementation of gender segreration itself in the education world. In this research, the researcher raised the theme of Islamic education as the location of conducted research at MA Raudlatul Ulum. Islamic education is a holistic education that oriented to whole system, not only its components but its students including values, morality, and skills. This research study uses qualitative with phenomenological methods. In the process of collecting data, the methods used are interviews, participatory observation, documentation and data analysis using context analysis. This research procedure is the stage of research process through analysis of learning management and student learning outcomes, analyzing gender responsive forms and the last is evaluating learning management based on gender responsive segregation. The result of this research shows that learning management conducted at MA Raudlatul Ulum is gender responsive with the implementation of planning in stages that takes into account gender responsive aspects. Then, the process of implementing learning management did not find material that marginalized and streotyped, and was proven by the successful learning outcomes of students.